qanda-logo
apple logogoogle play logo

Calculator search results

Formula
Solve the quadratic equation
Answer
circle-check-icon
expand-arrow-icon
expand-arrow-icon
expand-arrow-icon
expand-arrow-icon
expand-arrow-icon
expand-arrow-icon
$$x ^ { 2 } + 4 x - 5 = 0$$
$\begin{array} {l} x = 1 \\ x = - 5 \end{array}$
Calculate using the quadratic formula
$\color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { - 4 \pm \sqrt{ 4 ^ { 2 } - 4 \times 1 \times \left ( - 5 \right ) } } { 2 \times 1 } }$
$ $ Organize the expression $ $
$\color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { - 4 \pm \sqrt{ 36 } } { 2 \times 1 } }$
$x = \dfrac { - 4 \pm \sqrt{ \color{#FF6800}{ 36 } } } { 2 \times 1 }$
$ $ Organize the part that can be taken out of the radical sign inside the square root symbol $ $
$x = \dfrac { - 4 \pm \color{#FF6800}{ 6 } } { 2 \times 1 }$
$x = \dfrac { - 4 \pm 6 } { 2 \color{#FF6800}{ \times } \color{#FF6800}{ 1 } }$
$ $ Multiplying any number by 1 does not change the value $ $
$x = \dfrac { - 4 \pm 6 } { \color{#FF6800}{ 2 } }$
$\color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { - 4 \pm 6 } { 2 } }$
$ $ Separate the answer $ $
$\begin{array} {l} \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { - 4 + 6 } { 2 } } \\ \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { - 4 - 6 } { 2 } } \end{array}$
$\begin{array} {l} x = \dfrac { \color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ + } \color{#FF6800}{ 6 } } { 2 } \\ x = \dfrac { - 4 - 6 } { 2 } \end{array}$
$ $ Add $ - 4 $ and $ 6$
$\begin{array} {l} x = \dfrac { \color{#FF6800}{ 2 } } { 2 } \\ x = \dfrac { - 4 - 6 } { 2 } \end{array}$
$\begin{array} {l} x = \color{#FF6800}{ \dfrac { 2 } { 2 } } \\ x = \dfrac { - 4 - 6 } { 2 } \end{array}$
$ $ Do the reduction of the fraction format $ $
$\begin{array} {l} x = \color{#FF6800}{ \dfrac { 1 } { 1 } } \\ x = \dfrac { - 4 - 6 } { 2 } \end{array}$
$\begin{array} {l} x = \color{#FF6800}{ \dfrac { 1 } { 1 } } \\ x = \dfrac { - 4 - 6 } { 2 } \end{array}$
$ $ Reduce the fraction to the lowest term $ $
$\begin{array} {l} x = \color{#FF6800}{ 1 } \\ x = \dfrac { - 4 - 6 } { 2 } \end{array}$
$\begin{array} {l} x = 1 \\ x = \dfrac { \color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ - } \color{#FF6800}{ 6 } } { 2 } \end{array}$
$ $ Find the sum of the negative numbers $ $
$\begin{array} {l} x = 1 \\ x = \dfrac { \color{#FF6800}{ - } \color{#FF6800}{ 10 } } { 2 } \end{array}$
$\begin{array} {l} x = 1 \\ x = \color{#FF6800}{ \dfrac { - 10 } { 2 } } \end{array}$
$ $ Do the reduction of the fraction format $ $
$\begin{array} {l} x = 1 \\ x = \color{#FF6800}{ \dfrac { - 5 } { 1 } } \end{array}$
$\begin{array} {l} x = 1 \\ x = \dfrac { - 5 } { \color{#FF6800}{ 1 } } \end{array}$
$ $ If the denominator is 1, the denominator can be removed $ $
$\begin{array} {l} x = 1 \\ x = \color{#FF6800}{ - } \color{#FF6800}{ 5 } \end{array}$
Try more features at Qanda!
Search by problem image
Ask 1:1 question to TOP class teachers
AI recommend problems and video lecture
apple logogoogle play logo